Integracija vadbenih postaj za ravnotežje v bivalno okolje starejših - Kovač, Lucija (Šport (Ljubljana), 2021)
The aim of the study was to examine the effects of the integration of balance training stations in the living environment of the elderly people. The study involved 25 elderly people (86,5 +- 3,8years), who lived in a senior citizens home in Fužine. The exercise group was using the integraded balance training stations. During the intervention we monitored how the elderly liked the exercises, how difficult it seemed to them and how many exercises were they performing during the week. The results showed that elderly had similar views toward exercise, regardless of the complexity of the exercise itself and the week in which they performed the exercise. In the results of the use of the track, the share of the use of lighter exercises decreased over four weeks, while the share of the use of heavier exercises increased. The integration of balance training stations into the living environment can have a positive effect on improving the balance of the elderly and thus act as a prevention against falls. Group implementation of exercises encourages peer cooperation and has a positive effect on social inclusion and loneliness, which is especially important for the elderly who live in nursing homes.
Keywords: balance; elderly; exercise stations; integracija; integration; physical acivity; ravnotežje; sport; stališča; starostniki; šport; telesna aktivnost; vadbene postaje